Efficient syntheses of climate relevant isoprene nitrates and (1R,5S)-(−)-myrtenol nitrate - Bew, Sean P (Beilstein J Org Chem, 2016)
Here we report the chemoselective synthesis of several important, climate relevant isoprene nitrates using silver nitrate to mediate a ’halide for nitrate’ substitution. Employing readily available starting materials, reagents and Horner–Wadsworth–Emmons chemistry the synthesis of easily separable, synthetically versatile ‘key building blocks’ (E)- and (Z)-3-methyl-4-chlorobut-2-en-1-ol as well as (E)- and (Z)-1-((2-methyl-4-bromobut-2-enyloxy)methyl)-4-methoxybenzene has been achieved using cheap, ’off the shelf’ materials. Exploiting their reactivity we have studied their ability to undergo an ‘allylic halide for allylic nitrate’ substitution reaction which we demonstrate generates (E)- and (Z)-3-methyl-4-hydroxybut-2-enyl nitrate, and (E)- and (Z)-2-methyl-4-hydroxybut-2-enyl nitrates (‘isoprene nitrates’) in 66–80% overall yields. Using NOESY experiments the elucidation of the carbon–carbon double bond configuration within the purified isoprene nitrates has been established. Further exemplifying our ‘halide for nitrate’ substitution chemistry we outline the straightforward transformation of (1R,2S)-(−)-myrtenol bromide into the previously unknown monoterpene nitrate (1R,2S)-(−)-myrtenol nitrate.